MOTOR DEVELOPMENT AND ACADEMIC ACHIEVEMENT. IS THERE A RELATIONSHIP IN CHILDREN AND YOUNGSTERS? - Saraiva, João Paulo; Rodrigues, Luís Paulo (Portuguese Journal of Education, 2011)
A holistic perspective of the human development needs to look for every element responsible for the individual success. Surely between those, motor development for its relation with healthy lifestyles, and academic achievement due to its social relevance, constitute two major determinants of future success in life. The aim to this article was to review the major contributions found in the scientific literature of the last decade that can help us to better understand the possible relationship between motor development success and academic achievement in children and adolescents. Keywords Motor development; Academic achievement; Children; Adolescents